Strengthening the Role of ASPETRI East Java in Indonesian Herbal Medicine: Training New Members for the Sustainability of Natural Medicine Development in Indonesia - Wibowo, Teguh Setiawan; Larasaty, Hartaty; Lazuardi Ramadhan, Moh Risqy (Jurnal Pengabdian West Science, 2025)
ASPETRI (Indonesian Traditional Herbal Practitioners Association) East Java plays a strategic role in the preservation and development of natural medicines based on local wisdom. This article discusses the training program for new ASPETRI members as an effort to strengthen the organization's role in Indonesian herbal medicine. The training covers both theoretical and practical aspects, including the identification of medicinal plants, herbal formulation, and their evidence-based scientific applications. The methods used in this program include training sessions, workshops, and mentorship by experts in herbal. The outcomes of this training are expected to enhance the competence of new members, ensure the sustainable use of safe and effective herbal medicine, and encourage innovation in the development of natural drugs. Thus, ASPETRI East Java continues to contribute to improving the quality of traditional medicine and integrating it into the national healthcare system.